Cloacal microbiota of barn swallows from Northern Italy. Issue 4 (4th July 2018) - Musitelli, Federica; Ambrosini, Roberto; Rubolini, Diego; Saino, Nicola; Franzetti, Andrea; Gandolfi, Isabella
Abstract : Bird gut microbiota shows large variation among geographical populations of the same species – probably because, differently from mammals, gut microbiota of birds is largely affected by extrinsic factors such as diet and environmental conditions. We analysed the cloacal microbiota (CM) of 12 barn swallows ( Hirundo rustica ) from a colony in Northern Italy by high-throughput DNA sequencing of the 16S rRNA gene. The CMs, dominated by bacteria of the phyla Proteobacteria, Actinobacteria, Firmicutes and Bacteroidetes, did not significantly differ between adult females, adult males and fledglings. This first description of barn swallow CM in Italy, together with two previous studies from Europe, suggests that CMs of geographically different barn swallow populations are dominated by bacteria belonging to the same phyla but different genera. The intra-colony similarity of the CMs may be due to the exposure of individuals to the same local environmental conditions while on their breeding grounds.